PHOTOSYNTESIS OF SOYBEAN SINGLE LEAF INRELATION TO LIGHT INTENSITY AND LEAF TEMPERATURE - Yonny Koesmaryono; Daijiro Ito; Hideki Sukimoto; Tetsuya Haseba; Haruo Suzuki (Agromet, 1995)
Abstract is available in the full text (pdf format)